STRATEGI PEMBUATAN AKUN MARKET PLACE UNTUK UMKM PADA ORGANISASI ORKI TANGERANG SELATAN - Mada Faisal Akbar; Purwanti; Arif Hidayat (Abdi Jurnal Publikasi, 2025)
The Internet as part of a Marketing Communication program can be a useful tool in terms of branding. It is unfortunate that many companies have not yet discovered how to become a successful brand through the internet. The virus of social networking makes internet users attractive and marketers intend to spread information by word of mouth. Marketplace is an online intermediary for sellers and buyers. Sellers can sell their merchandise in a marketplace along with other sellers who may sell similar or different items. Then, buyers can also search for the items they want through the marketplace. In essence, a marketplace is a place to sell online that combines several sellers and product brands